2012
DOI: 10.1093/ndt/gfs460
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Klotho and FGF23 in chronic kidney disease Stage 1 to 5: a sequence suggested from a cross-sectional study

Abstract: Soluble Klotho and 1,25D levels decrease and FGF23 levels increase at early CKD stages, whereas PTH levels increase at more advanced CKD stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
135
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(158 citation statements)
references
References 36 publications
12
135
2
5
Order By: Relevance
“…Clinical and experimental animal studies showed low renal tubular aKlotho expression in both acute kidney injury and CKD 10,40,42,43,[56][57][58][59][60][61][62] and low circulating aKlotho levels in kidney diseases of a variety of etiologies in animals 42,43,56,62 and humans. 32,44,61,63 These data suggest that the kidney contributes to circulating aKlotho. Now we provide direct experimental evidence that the kidney is the source of circulating aKlotho by demonstrating step-up of aKlotho concentration from infrarenal to suprarenal vena cava in both mice and humans.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Clinical and experimental animal studies showed low renal tubular aKlotho expression in both acute kidney injury and CKD 10,40,42,43,[56][57][58][59][60][61][62] and low circulating aKlotho levels in kidney diseases of a variety of etiologies in animals 42,43,56,62 and humans. 32,44,61,63 These data suggest that the kidney contributes to circulating aKlotho. Now we provide direct experimental evidence that the kidney is the source of circulating aKlotho by demonstrating step-up of aKlotho concentration from infrarenal to suprarenal vena cava in both mice and humans.…”
Section: Discussionmentioning
confidence: 78%
“…26,29 The kidney has the highest level of expression of aKlotho, but it is important to know whether aKlotho circulating in serum is derived from the kidney. Serum aKlotho levels in patients with CKD are extremely variable [30][31][32][33][34][35][36][37][38][39] probably due to assay-related variance. In contrast, renal aKlotho levels are uniformly reduced in CKD.…”
mentioning
confidence: 99%
“…36,37 In this study, we observed that the decrease of serum Klotho was closely related with the decline of eGFR in patients with CKD, which is in accordance with previous reports. 38,39 However, a recent study performed by Seiler et al 40 showed that the plasma level of Klotho was not related to renal function in patients with CKD stages 2-4. We agree with the opinion that the discrepancy is probably caused by the study design and sampling strategies, including proportion of patients with different CKD stages, exclusion of specific intervention factors, and samples prepared from serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 is increased in CKD, 25,59 but the mechanism of the increase is not entirely known. Circulating and renal Klotho deficiency precedes the increase in plasma FGF23 25,60 and is a potential mechanism of stimulating FGF23.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating and renal Klotho deficiency precedes the increase in plasma FGF23 25,60 and is a potential mechanism of stimulating FGF23. 17,36 The role of FGF23 in mediation of cardiac hypertrophy was suggested by epidemiologic data 30,[61][62][63] and strongly suggested by an animal study.…”
Section: Discussionmentioning
confidence: 99%